Policy Regarding Increased Control of Circulation or Trade of Dog Meat in Karanganyar Regency (Reviewed through the concept of Animal Welfare and The Rule of Adz-Dzariah Fiqh) - Enggarani, Nuria Siswi; Nugroho, Wisnu Tri (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2020)
Objective: This study aims to determine the implementation of policies regarding increasing supervision of the distribution or trade of dog meat in Karanganyar regency and to find out the policy review through the concept of animal welfare and adz-dzariah rules. Methodology: This research is a juridical-empirical method, with the type of research being analytic descriptive, and the data collection method used is library research and field research. Finding: This research shows that the implementation of policies regarding the increase of supervision on the distribution or trade of dog meat in Karanganyar is divided into the stages of pre-implementation, implementation, and post-implementation. The policy is also a step towards realizing the concept of Animal Welfare because this policy will stop the torture of dogs. In contrast, in the rule of adz-dzari'ah fiqh, the implementation of the policy is to implement the sharia maqashid, which aims to protect Al-Kulliyah Al-Khamsah. Application of the Study: The policy on increasing supervision of the distribution or trade of dog meat is essentially to prevent the spread of zoonoses and stop the practice of violence against dogs. While this research is expected to provide an overview and information on the implementation of the policy. Originality/Novelty: This research can be categorized differently from previous studies, where this research is more focused on the implementation of policies in Karanganyar which are then analyzed with the concept of Animal Welfare and the rule of adz-dzari'ah fiqh. Keywords: Adz-Dzari’ah, Animal Welfare, Policy, Maqashid Syari’ah